Inner resonance and outer current based control strategy for inductive power transfer system used in wireless charging for electric vehicles - Varikkottil, Sooraj; Lionel, Febin Daya John; Srinivasan, Mohan Krishna; Perumal, Thinagaran; Stonier, Albert Alexander; Peter, Geno; Pagidi, Balachennaiah; Ganji, Vivekananda (John Wiley and Sons, 2024)
The wireless charging for electric vehicle is getting popular due to the absence of sophisticated cable connection and associated issues with the actuators in field for connected charging. The major challenges in inductive power transfer (IPT) systems are the control of the resonance converter and synchronisation in communications with the vehicle and power supply. In IPT system, the dynamic nature of load as well as system demands extra care for the existing charging architectures. This work proposes a unique control algorithm to charge the Li-ion battery under coupling coefficient and load variations. The developed control algorithm is validated in MATLAB simscape platform. Further, the control logic is validated using the Texas C2000 Delfino controller in 1 kW IPT system. The developed control logic would ensure proper frequency of operation as well as the constant voltage and constant current control.